2018
DOI: 10.1088/1742-6596/1013/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of 3D virtual learning environment to improve students’ cognitive achievement

Abstract: Abstract. Virtual Learning Environment (VLE) has been widely used in assisting learning. This study aims to implement VLE-based learning in software engineering course. VLE provides many facilities for learning. In this research, VLE components used were presenter and quiz chair components. Evaluation results showed a significant difference from classical learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A study by Simsek (2016) concluded that virtual reality increased students' positive attitudes and interest in mathematics. A study by Rasim et al (2017) found that Implementation of the 3D virtual learning environment can improve students' cognitive achievement in software engineering courses. A study by Bogusevschi, et al, (2020) showed that using a 3D virtual learning environment in teaching physics support students to gain a high experience score.…”
Section: Three-dimensional Virtual Learning Environmentmentioning
confidence: 99%
“…A study by Simsek (2016) concluded that virtual reality increased students' positive attitudes and interest in mathematics. A study by Rasim et al (2017) found that Implementation of the 3D virtual learning environment can improve students' cognitive achievement in software engineering courses. A study by Bogusevschi, et al, (2020) showed that using a 3D virtual learning environment in teaching physics support students to gain a high experience score.…”
Section: Three-dimensional Virtual Learning Environmentmentioning
confidence: 99%
“…Due to the limited usage of VLE in secondary level education (Pei, 2017a), there is still a dearth of research on the topic, with the majority of it being found at postsecondary educations (Aditya et al, 2019;Rasim et al, 2018;Rojabi, 2020). Numerous research on VLE continue to emphasize technology design, teachers conduct, and skills gain e d from utilizing VLE.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies (Aditya et al, 2018, Rasmitadila et al, 2020 explain how technology design readiness enhances teacher behavior while using VLE, while other studies cover the implementation of VLE use in an effort to raise students' motivation, thinking abilities, and independence. to understand (Rasim et al, 2018;Rasmitadila et al, 2020;Rojabi, 2020;Rosyadi et al, 2021). Similarly, research on e-leadership in relation to VLE is currently quite scarce.…”
Section: Introductionmentioning
confidence: 99%